The influence of subsurface damage depth on fracture strength of ground silicon wafers. (2022) - Dai, Siyang; Zhou, Ping; Guo, Dongming
Abstract: A grinding process is required to thin the back of the semiconductor chips to meet the requirements of chip thickness. Subsurface damage caused by the grinding can result in fracture strengths degradation, which has an impact on the safety and reliability of the chip. In this paper, the fracture strengths of silicon wafers ground using wheels with different grit size were obtained by the ball-on-ring method, and the Weibull distribution function was used to fit the fracture strengths. The subsurface damage depths at different radial positions of the ground silicon wafer were measured by cross-section polishing microscopy. Results showed that the fracture strengths decreased with the increase of subsurface damage depths, and the relationship between the fitted minimum strength and the maximum depth of subsurface damage was in good agreement with the prediction result of the classical fracture mechanics formula.